A Framework for the Integration of Performance Based Design and Life Cycle Assessment to Design Sustainable Structures. Issue 4 (April 2014) - Zhao, X.L.; Li, W.; Stanbrook, J.
Sustainability is an issue that has become of key importance to the engineering industry. An important definition for sustainability is True Sustainability: a concept often termed the Triple Bottom Line Approach, which involves the balance of Economic, Social and Environmental sustainability. At present the focus on sustainable design within the engineering profession is on Environmental Sustainability and Green Design. This focus is too narrow with engineering systems not considering the other components of sustainability emphasizing the need for sustainable design to have a broader scope. This paper presents a framework attempting to overcome this narrow focus through the integration of two separate engineering design techniques, Performance Based Design and Life Cycle Assessment. The framework is a 6-step process that combines these two techniques through establishment of common goals. This integration presents a logical methodology that may be adopted by engineering professionals to design engineering systems to achieve True Sustainability. This framework will have several implications for the engineering field including changes to the current design-construction process and education of engineers. The framework is a base for continued research on how to implement design techniques into the engineering industry to enhance the sustainability of constructed systems.